Severe Diesel Injection Injury to the Face, Neck and Orbit: Surgical Management and Critical Care Considerations. Issue 6 (20th May 2022) - Dawson, Valerie J.; Lacey Echalier, E.; Vu, Brian; Liao, Sophie; Goddard, Julie; Hink, Eric
Abstract : The purpose of this report is to discuss high-pressure injection injuries involving the face and orbit and discuss factors affecting prognosis and management as these injuries are rare and uniquely challenging to manage given the complex anatomy and extensive damage that may occur. In this case, we present severe injury to the left orbit, maxillofacial region, and neck of a 29-year-old male who suffered a high-pressure diesel injection injury requiring several surgical debridements, intensive care unit (ICU) level care, and ultimately sub-total exenteration. Initial management involved systemic antibiotics, steroids, and surgical debridement; however, our patient experienced subsequent rapid deterioration resulting in admission for more aggressive subspecialty intervention. Decision-making was guided by serial CT of the face and orbits, and C-reactive protein (CRP) levels in addition to the physical examination. His course was complicated by progressive extensive soft tissue necrosis requiring 8 surgical debridements and optic nerve tenting despite orbital decompression resulting in loss of the OS. Ultimately, definitive treatment required sub-total exenteration and negative wound pressure therapy over the orbit followed by eyelid reconstruction as an outpatient. We conclude that without prompt recognition and meticulous debridement, the resultant injury from high-pressure injection injuries can be devastating and lead to permanent vision loss, loss of an eye, loss of facial function, and airway compromise depending on the location of the injury. A multi-disciplinary team involving oculoplastics, otolaryngology, infectious disease, and ICU should be assembled based on the complexity of this injury and its sequela. CRP can be useful to monitor patient recovery and the need for further surgical intervention. When debridement results in complex wounds over the orbit and face, negative pressure wound therapy should be considered. Abstract : High-pressure injection injuries involving the face and orbit require prompt recognition, and meticulous surgical debridement, clinical course monitoring is aided by CRP, and negative pressure wound therapy aids healing of complex wounds.